2014
DOI: 10.1063/1.4880055
|View full text |Cite
|
Sign up to set email alerts
|

High and low frequency instabilities driven by counter-streaming electron beams in space plasmas

Abstract: A four-component plasma composed of a drifting (parallel to ambient magnetic field) population of warm electrons, drifting (anti-parallel to ambient magnetic field) cool electrons, stationary hot electrons, and thermal ions is studied in an attempt to further our understanding of the excitation mechanisms of broadband electrostatic noise (BEN) in the Earth's magnetospheric regions such as the magnetosheath, plasmasphere, and plasma sheet boundary layer (PSBL). Using kinetic theory, beam-driven electrostatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The general trend observed in Fig. 7(d) that the cool electron density at which the switch to positive polarity solitons occurs increases with the drift velocity is explained in terms of the large magnitude of the sum of the positive signed contributions of the warm and hot electrons in (11), which will require a large density of the cool electrons n ce0 [negative signed contribution to (11)] to reduce the (positive signed) contribution of the hot electrons, for balance. The (positive signed) contribution of the ions (fourth term) is negligible in that it can be ignored because of the large ion to electron mass ratio (l i ¼ 1836).…”
Section: Numerical Results and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The general trend observed in Fig. 7(d) that the cool electron density at which the switch to positive polarity solitons occurs increases with the drift velocity is explained in terms of the large magnitude of the sum of the positive signed contributions of the warm and hot electrons in (11), which will require a large density of the cool electrons n ce0 [negative signed contribution to (11)] to reduce the (positive signed) contribution of the hot electrons, for balance. The (positive signed) contribution of the ions (fourth term) is negligible in that it can be ignored because of the large ion to electron mass ratio (l i ¼ 1836).…”
Section: Numerical Results and Discussionmentioning
confidence: 84%
“…The value v dbw0 ¼ 1:084 at which a switch to positive polarity solitons occurs is close to the minimum threshold value v dbw0 ¼ 1:094 for which the slow electronacoustic mode becomes unstable. We recall that the sign of (11) gives the polarity of small amplitude solitons. The vanishing of the third derivative of the Sagdeev potential (d 3 VðUÞ=dU 3 Þ U¼0 ¼ 0) at v dbw0 ¼ 1:084 and the reduction (increase) in the width of the soliton M ranges for v dbw0 < 1:084 (v dbw0 > 1:084) near v dbw0 ¼ 1:084 are consistent with a very large number of studies 14,15,[18][19][20] in which polarity switches have been reported for electron-acoustic solitons.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, magnetized plasmas often experience counterstreaming along the ambient magnetic field, modifying a plasma velocity distribution function to a counterstreaming bi-Maxwellian or a counterstreaming kappa distribution function. In this case, much less results are available, especially as the analytical studies of the phenomena [21][22][23][24][25][26][27][28][29][30] are concerned. Since there is not yet a complete picture of kinetic instabilities in plasmas with counterstreaming distribution functions, the present manuscript might make a certain contribution to this field of researches.…”
Section: Introductionmentioning
confidence: 99%